2018
DOI: 10.1016/j.pharmthera.2017.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Bevacizumab-induced hypertension: Clinical presentation and molecular understanding

Abstract: Bevacizumab is a vascular endothelial growth factor-A-specific angiogenesis inhibitor indicated as an adjunct to chemotherapy for the treatment of several types of cancer. Hypertension is commonly observed during bevacizumab treatment, and high-grade toxicity can limit therapy and lead to other cardiovascular complications. The factors that contribute to interindividual variability in blood pressure response to bevacizumab treatment are not well understood. In this review, we outline research efforts to unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
83
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(95 citation statements)
references
References 124 publications
0
83
1
2
Order By: Relevance
“…Therefore, we studied plasma and lung specimens from patients treated with bevacizumab, a humanized monoclonal antibody directed against VEGF. Cardiovascular side-effects of bevacizumab include thromboembolic events [22,41], ischemic events [10,41], hypertension [16,28,55], pulmonary embolism [22,39,41] and pulmonary hypertension [29]. The mechanism of these bevacizumab-related cardiovascular events is not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we studied plasma and lung specimens from patients treated with bevacizumab, a humanized monoclonal antibody directed against VEGF. Cardiovascular side-effects of bevacizumab include thromboembolic events [22,41], ischemic events [10,41], hypertension [16,28,55], pulmonary embolism [22,39,41] and pulmonary hypertension [29]. The mechanism of these bevacizumab-related cardiovascular events is not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently it has been approved as part of a combination therapy in the treatment of various cancers, including metastatic lung, colorectal, and renal cell carcinoma, and as a single agent treatment in adult glioblastoma [37]. However, subsequent studies have revealed adverse effects, including gastrointestinal perforation, nephrotic syndrome, thromboembolism, surgical wound healing complications and hypertension [37,38].…”
Section: Introductionmentioning
confidence: 99%
“…Quanto à hipertensão arterial, alguns quimioterápicos estão diretamente relacionados ao desenvolvimento ou piora da hipertensão pré-existente, por exemplo, os inibidores do fator angiogênico (anti-VEGF), como o Bevacizumabe [32][33] . Este anticorpo monoclonal é indicado, atualmente, como primeira linha do tratamento do câncer colorretal mestastático [32][33] e as taxas de hipertensão associadas ao uso deste quimioterápico vão de 4% a 35% dos pacientes 34 . Dado o seu mecanismo de ação, ocorre vasoconstrição sistêmica, com consequente ativação do sistema renina-angiotensina-aldosterona e desenvolvimento e/ou complicação da hipertensão arterial 32,34 .…”
Section: Discussionunclassified